Psychological wellbeing among hostel students of selected hostel of Lalitpur. - Koirala,Kanchan (2018)
ABSTRACT: Mental health problem is one of the most neglected issues among adolescents. Various studies have concluded the important effect of well-being on mental health. Many studies have been conducted to find out the psychological well-being among adolescents but very less is known about the psychological well-being of hostel students. The objective of this study was to identify the psychological well-being among hostel students. Descriptive cross sectional research design was used in this study. The research was conducted in Little Angels College. The population for this study included all the students who were enrolled in hostel during the time of data collection at Little Angels College. A probability simple random technique was used to select the sample. Anonymity and confidentiality was maintained. Data was collected using self-administered structured questionnaire; Ryff's Psychological WellBeing Scale developed by Carol Ryff. Data was analyzed by using descriptive statistics such as frequency, percentage, mean and standard deviation and inferential statistics such as t-test to find out association between selected variables. Findings of the study showed that majority of the respondents 51.2% were in the middle of the distribution, only 22.8% of them had high Psychological well-being and 26% had low Psychological well-being. There was statistically significant association between Psychological well-being and satisfaction with academic performance (P=0.001), help from friends regarding studies (P=0.008), faculty chosen (P=0.001) and physical health problems (P=0.002). Findings of study concluded that the majority of the respondent's psychological wellbeing was in middle of the distribution followed by low psychological well-being and very few respondents had high psychological well-being. Improving the quality or provision of facilities, peer support and good academic performance of students in hostels will enhance the psychological well-being of hostellers. So, counseling programs should be launched so that the hostel students can verbalize their feelings. Keywords: Hostel students, Psychological well-being